Clinical proteomics stretch goals: EuPA 2012 roundtable report - O'Neil, S.E. (2014)
The field of clinical proteomics is faced with multiple challenges which need to be overcome in order to improve our understanding of human diseases and provide management solutions. Researchers interested in clinical proteomics assembled for a roundtable discussion at the European Association for Proteomics (EuPA) conference held in Glasgow in July 2012, to discuss these challenges and highlight the key areas for successful clinical proteomic studies. This report shares topics of discussion and the resulting stretch goals of clinical proteomics for researchers to strive towards.